2017
DOI: 10.1111/1755-5922.12258
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level incidence and monitoring of adverse drug reactions with long‐term amiodarone therapy

Abstract: In this population-based study, adherence to laboratory monitoring guidelines was suboptimal. There was a positive correlation with total amiodarone exposure and biochemical abnormalities and development of thyroid disease compared to the general population, highlighting the need for improvement and continued amiodarone monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The current study found a low rate of CXR follow-up (47.6%), which is consistent with a previous publication (50%) [ 6 ]. A similar result was found regarding LFT follow-up performance (49%), which is in alliance with multiple previous publications (40.5, 52 and 46%) [ 6 , 7 , 9 ]. TFT follow-up was conducted for only 22.4% of the patients included in our study, which is of concern, but consistent with several published studies reporting 32, 20, 16.5 and 28% of TFT follow-up performances [ 6 , 7 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study found a low rate of CXR follow-up (47.6%), which is consistent with a previous publication (50%) [ 6 ]. A similar result was found regarding LFT follow-up performance (49%), which is in alliance with multiple previous publications (40.5, 52 and 46%) [ 6 , 7 , 9 ]. TFT follow-up was conducted for only 22.4% of the patients included in our study, which is of concern, but consistent with several published studies reporting 32, 20, 16.5 and 28% of TFT follow-up performances [ 6 , 7 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Forty-eight percent of the patients performed CXR and all patients (100%) conducted ECG [ 8 ]. According to a study performed by Rankin et al, (2017), the recorded adherence was 46% for liver and 28% for thyroid baseline assessments [ 9 ]. The current study found a low rate of CXR follow-up (47.6%), which is consistent with a previous publication (50%) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the choice of antiarrhythmia medication, long-term monitoring and patient education is required. This finding is supported by the longitudinal, retrospective population-based study by Rankin et al (2016) that found poor adherence to monitoring guidelines in relation to long-term amiodarone treatment. Toxicity of the thyroid, liver, and lungs were the most common adverse drug reaction with amiodarone.…”
Section: Theme One: Living With Atrial Fibrillationsupporting
confidence: 54%
“…thyroid), whereas others may take years to be manifested and occur in a cumulative dose-dependent fashion. [18][19][20] Monitoring of the Patient Receiving Longterm Amiodarone Therapy If amiodarone use is longer than 3 months, the following baseline tests should be obtained: ECG for QT prolongation (avoid if QTc >500 milliseconds) and AV block (avoid if second-degree type II or greater); thyroid function test; liver function test; pulmonary function test; chest radiograph; formal ophthalmologic examination; and initial skin examination. Thyroid and liver function testing should be performed every 6 months.…”
Section: Systemmentioning
confidence: 99%